Soil transmitted Helminthiasis and associated risk factors among elementary school children in ambo town, western Ethiopia - Fikreslasie Samuel; Asalif Demsew; Yonas Alem; Yonas Hailesilassie (BMC, 2017)
Abstract Background Soil-transmitted helminths (STHs) are widespread in underdeveloped countries. In Ethiopia, the prevalence and distribution of helminth infection varies by different exposing risk factors. We therefore investigated the prevalence of and risk factors of STHs infection in school children living in Ambo town, west Shoa Ethiopia. Methods In 2014/15, among 375 school children planed to be included in this study, only 321 school children were recruited in the study. Data onto school children from different schools were collected, including stool samples for qualitative STHs analysis. Questionnaire data on various demographic, housing and lifestyle variables were also available. Results Prevalence of any STHs infection was 12.6%. The respective prevalence of major soil-transmitted helminths is Ascaris (7.8%), Hookworm (2.8%) and Trichuris (2.2%). This study result shows STHs prevalence varies regards to age, sex, latrine use, family size and nail trimming. Conclusion The results of the present study indicated that the percentage of positive finding for STHs in Ambo area is low. Besides, Large Family size, not nail trimming and unavailability of improved latrine were identified as predisposing factor for STHs infections. All school children enrolled and not enrolled in this study should be treated twice a year until the prevalence falls below the level of public health importance.